2007
DOI: 10.1016/j.vetmic.2007.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Shiga-Toxin producing Escherichia coli (STEC) and bovine feces background microflora in various enrichment protocols

Abstract: Cattle are an important reservoir for STEC and eating food contaminated with fecal material is a frequent source of human STEC infection. It is thus essential to reliably determine the prevalence of STEC contamination in cattle. Currently, different enrichment protocols are used before the detection of Shiga-Toxin producing Escherichia coli (STEC) in fecal samples. However, there have not been any studies performed that have compared the effectiveness of these various enrichment protocols for the growth of non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…E2 was degraded to below the detection limit within approximately 9 h in systems directly inoculated with swine manure (system 1), but only 20% of the E2 was degraded within the same incubation period in systems inoculated with TSB pre‐enriched microbial cultures (system 2) despite the higher cell density. The most likely reason for the slower and different (zero‐ vs. pseudo first‐order kinetics) degradation pattern in system 2 is that the TSB pre‐enrichment disfavored the bacteria that were responsible for the rapid degradation in system 1 (Vimont et al, 2007). The relative degradation rates of E2, testosterone, and progesterone observed in system 1 (E2 > progesterone > testosterone) are in contrast to results obtained from studies conducted with soils, biosolids, and swine manure‐applied soils, broiler litter, and composted chicken ( Gallus gallus ) manure (Casey et al, 2004; Ermawati et al, 2007; Hakk et al, 2005; Hemmings and Hartel, 2006; Jacobsen et al, 2005; Lee et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…E2 was degraded to below the detection limit within approximately 9 h in systems directly inoculated with swine manure (system 1), but only 20% of the E2 was degraded within the same incubation period in systems inoculated with TSB pre‐enriched microbial cultures (system 2) despite the higher cell density. The most likely reason for the slower and different (zero‐ vs. pseudo first‐order kinetics) degradation pattern in system 2 is that the TSB pre‐enrichment disfavored the bacteria that were responsible for the rapid degradation in system 1 (Vimont et al, 2007). The relative degradation rates of E2, testosterone, and progesterone observed in system 1 (E2 > progesterone > testosterone) are in contrast to results obtained from studies conducted with soils, biosolids, and swine manure‐applied soils, broiler litter, and composted chicken ( Gallus gallus ) manure (Casey et al, 2004; Ermawati et al, 2007; Hakk et al, 2005; Hemmings and Hartel, 2006; Jacobsen et al, 2005; Lee et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…IMS appears to be less sensitive for detection than RT-PCR (4,72). Even though detection and strain isolation are not comparable, it must be emphasized that STEC isolation methods are substantially less sensitive than molecular methods for detecting these pathogens (52).…”
Section: Discussionmentioning
confidence: 97%
“…The protocol developed to detect E. coli O26 in raw milk cheeses is very efficient and easy to use in routine diagnostic procedures with the added benefit that it could be available to the cheese industry as a bivalent detection approach permitting E. coli O26 and O157 detection from the same enrichment. Indeed, numerous studies have shown that E. coli O157:H7 strains could grow on cefixim–tellurite‐supplemented media (Vimont et al. 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In raw milk cheeses, the presence of high levels of background flora can influence the growth of STEC (Vimont et al. 2007) and make difficult its subsequent detection.…”
Section: Introductionmentioning
confidence: 99%